APPLICATION PROGRAM OF GOODS IN JAKARTA DOCUMENTING TANJUNG PRIOK WAREHOUSE PREMIER OIL NATUNA BV JAKARTA SEA BY USING VISUAL BASIC 6.0 - Fivin Ervina; Yulina Yulina, Skom, MMSI (Jurnal Sistem Informasi, 2005)
This application is made to facilitate the activities of the activities in the TanjungPriok Jakarta Warehouse, is expected to ease in data collection on goods andminimize the occurrence of errors in the records of existing goods.Besides these applications is expected to assist in searching data that can shorten thetime in looking for a data item, if necessary.